Separate issues of qualification of unlawful actions committed in the sphere of equity participation in the construction of residential property - Zhunisbekov, N.N. (Bulletin of the Karaganda University “Law Series”, 2018)
This article describes the current state of law enforcement practice of crimes in the sphere of equity participation in the construction of residential facilities in the Republic of Kazakhstan. In the modern period, special attention is paid to the level of crime in this sphere of social relations. As applied to the subject of the study, there are a number of problems related to the qualification and definition of investigative jurisdiction under shared construction of residential facilities. Acquisition and disposition of residential property is an important and responsible moment in the life of each person, because often for many it (real estate) is the only vital value. The high cost of real estate and its invaluable social significance causes the emergence around it of various kinds of intermediaries, criminal structures, the spread of fraud in this area, including in the sphere of equity participation in housing construction. In this article we will talk about swindling, committed in this social sphere, which has spread widely in the Republic of Kazakhstan and is classified as a category of difficultly provable criminal offenses. Analysis of law enforcement practice has shown that it is the misconduct of relevant state bodies, their erroneous actions that often predetermine the negative outcome of such a social phenomenon as the share participation in the construction of residential property.